Если a=b+1 Доказать что (a+b) (a^2+b^2) (a^4+b^4) (a^8+b^8) (a^16+b^16)=a^32+b^32

Если a=b+1 Доказать что (a+b) (a^2+b^2) (a^4+b^4) (a^8+b^8) (a^16+b^16)=a^32+b^32
Гость
Ответ(ы) на вопрос:
Гость
Если a=b+1, то a-b=1 домножим на 1 выражение: 1*(a+b)(a^2+b^2)(a^4+b^4)(a^8+b^8)(a^16+b^16)= =(a-b)(a+b)(a^2+b^2)(a^4+b^4)(a^8+b^8)(a^16+b^16)= =(a^2-b^2)(a^2+b^2)(a^4+b^4)(a^8+b^8)(a^16+b^16)= =(a^4-b^4)(a^4+b^4)(a^8+b^8)(a^16+b^16)= =(a^8-b^8)(a^8+b^8)(a^16+b^16)= =(a^16-b^16)(a^16+b^16)= =(a^32-b^32) - доказано
Не нашли ответ?
Ответить на вопрос
Похожие вопросы